CONCEPT, TYPES, TASKS AND MEANS OF PHYSICAL TRAINING OF YOUNG ATHLETES - O‘razbayev Jaxongir Temur o‘g‘li (American Journals Publishing, 2024)
Physical training of young athletes is considered one of the most important components of sports training and is understood as a process aimed at comprehensive development of the body, strengthening of health, improvement of physical abilities and creation of a solid functional base for all other types of training.
Keywords: Sport, young generation, physical fitness, physical ability.